2019
DOI: 10.1080/24750573.2019.1699738
|View full text |Cite
|
Sign up to set email alerts
|

Use of multisensory stimulation interventions in the treatment of major neurocognitive disorders

Abstract: OBJECTIVE: Behavioral and psychological symptoms of dementia (BPSD) are a heterogeneous constellation of non-cognitive symptoms and behaviours that can cause significant patient distress and present complex management challenges. Behavioural and pharmacological treatments are used to decrease the symptoms, preserve function and increase quality of life. In the treatment of individuals with a major neurocognitive disorder, non-pharmacological interventions are often preferred as first-line treatment over pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 53 publications
0
8
0
2
Order By: Relevance
“…While there is limited research in VR for explicitly embedding 'novel' multimodal approaches, there is a good body of research that acknowledges the value of multisensory design in interventions that support healthcare and promote wellbeing. Multisensory VEs have been used to reduce stress levels (Putrino et al, 2020), have shown potential for improved quality of life for people with dementia (Cheng, Baker & Dursun, 2019;Sánchez et al, 2013) and provided interventions for anxiety symptoms (Rajasekaran et al, 2011) and the profoundly disabled (Brooks, 2021). Although multisensory design has been embedded in VR/MR there is limited research focus on embedding or facilitating 'fused' sensory experiences, for example, synaesthetic approaches.…”
Section: Related Workmentioning
confidence: 99%
“…While there is limited research in VR for explicitly embedding 'novel' multimodal approaches, there is a good body of research that acknowledges the value of multisensory design in interventions that support healthcare and promote wellbeing. Multisensory VEs have been used to reduce stress levels (Putrino et al, 2020), have shown potential for improved quality of life for people with dementia (Cheng, Baker & Dursun, 2019;Sánchez et al, 2013) and provided interventions for anxiety symptoms (Rajasekaran et al, 2011) and the profoundly disabled (Brooks, 2021). Although multisensory design has been embedded in VR/MR there is limited research focus on embedding or facilitating 'fused' sensory experiences, for example, synaesthetic approaches.…”
Section: Related Workmentioning
confidence: 99%
“…Çoklu duyusal uyaran yöntemi, demanslı bireylerin bilişsel ve ruhsal belirtilerini azaltmak ve iyilik halini sürdürmek amacıyla görsel, dokunsal, işitsel veya koku uyaranları yoluyla iki veya daha fazla uygulamanın aynı anda kullanılması sonucu ortaya çıkan bir müdahale yöntemidir (Cheng et al, 2019). Bu yöntemin uygulanması için kullanılan yeni tekniklerden biri olan Snoezelen, 1970'lerde Hollanda'da ilk olarak öğrenme güçlüğü çeken bireylerde uygulanmıştır.…”
Section: çOklu Duyusal Uyaran Yöntemiunclassified
“…Ca spații activatoare putem cataloga spațiile proiectate pentru a stimula memoria senzorială și pe cea procedurală, care vor antrena, la rândul lor, memoria episodică și reconectarea cu sine, cu istoria personală și cu prezentul. Aici putem include și spațiile care mimează domenii ale orașului și satului din tinerețe (Baxter, 2018;Kotecki, 2018;Keenan, 2014), mediile multisenzoriale (Snoezelen.2020;Cheng, 2019).…”
Section: )unclassified